2020
DOI: 10.1071/an18535
|View full text |Cite
|
Sign up to set email alerts
|

Defoliation dynamics, pasture intake and milk production of dairy cows grazing lucerne pastures in a partial mixed-ration system

Abstract: The effect of lucerne pasture allocation on defoliation dynamics, pasture intake and animal production was investigated in a subtropical partial mixed-ration dairy system. The study took place at the Gatton Research Dairy, south-eastern Queensland, with a 28-day adaptation period followed by an 8-day treatment period during November and December 2016. Twenty-four multiparous Holstein Friesian dairy cows were offered 11 kg of dry matter (DM)/cow.day as partial mixed-ration dairy system, and four levels of daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Grazing management strategies that target high levels of utilisation have been shown to have negative impacts on pasture intake. Recently, Ison et al [6] found that low allocations resulted in high levels of pasture utilization and lower intake in cows grazing lucerne in partial mixed ration systems. The study identified that cows selectively grazed the top leafy portion of lucerne across the whole area of the paddock, before regrazing the residual 'stemmy' portion of pasture remaining in previously grazed areas of their current paddock [6].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Grazing management strategies that target high levels of utilisation have been shown to have negative impacts on pasture intake. Recently, Ison et al [6] found that low allocations resulted in high levels of pasture utilization and lower intake in cows grazing lucerne in partial mixed ration systems. The study identified that cows selectively grazed the top leafy portion of lucerne across the whole area of the paddock, before regrazing the residual 'stemmy' portion of pasture remaining in previously grazed areas of their current paddock [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ison et al [6] found that low allocations resulted in high levels of pasture utilization and lower intake in cows grazing lucerne in partial mixed ration systems. The study identified that cows selectively grazed the top leafy portion of lucerne across the whole area of the paddock, before regrazing the residual 'stemmy' portion of pasture remaining in previously grazed areas of their current paddock [6]. When grazing the top leafy stratum, both intake and diet quality were maximised, as cows removed larger bites from the top leafy stratum with a high leaf content relative to stem [6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations